Social Media as a Catalyst Among Student Organizations in a Selected University in China - CHENG, YAN (Pacific International Journal, 2024)
This paper presents a study that explores the role of social media as a catalyst among student organizations at Shandong University of Traditional Chinese Medicine (SDUTCM) in China. The research objectives are to examine the current landscape of student organizations, assess social media usage patterns, investigate the impact of social media on student engagement, identify challenges and opportunities, explore student perceptions and experiences, develop best practices and recommendations, and contribute to the broader understanding of social media in higher education. The research reveals a positive correlation between higher frequency of social media usage and increased student engagement in organization activities. This suggests that social media can serve as a catalyst for engagement within the unique academic context of SDUTCM. The study provides valuable insights into the relationship between social media and student organizations, contributing to the improvement of student engagement, organization efficiency, and the understanding of social media's role in higher education. It also highlights the university's progressive approach in leveraging technology for educational and organizational advancement while promoting responsible social media use. The findings have international relevance and can benefit universities and student organizations worldwide.